Carbonate Facies and Depositional Environment On Baturaja Formation, “Mk” Field, Jatibarang Sub-Basin. - Manwarjit, Manwarjit; Syafri, Ildrem; Mohamad, Febriwan; Ginanjar, Asep (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
Facies are defined as a rock body that have a combination of characteristics that are related to the physical, biological, or chemical aspects seen from rock lithology, sedimentary structures that distinguish the rock body from the rocks above, below or laterally in other parts (Walker, 1992). This paper aimed to determine the facies and depositional environment that developed in the upper part of Baturaja Formation. The facies distribution analysis can be used as an early interpretation for the characterization of carbonate reservoir. In this research, the facies and depositional environment analysis is carried out by integrating core data, thin section, and wireline log. Based on this analysis, it is identified that 4 facies were deposited in 4 different types of depositional environment and time, which are Facies Floatstone (Facies I), Facies Wackstone- Packstone (Facies II), Facies Floatstone- Framestone (Facies III), dan Facies Floatstone- Rudstone (Facies IV). All facies are correlated to every well using electrofacies analysis so that the facies distribution on every well can be shown. The output of facies distribution can be illustrated into a cross-section of well-correlation.Keywords: Characterization, Facies distribution, Electrofacies, Well-correlation